Study Perception and Motivation Research in Learning Biology - Nadia Olivia; Relsas Yogica; Indra Hartanto; Lufri Lufri (ATRIUM PENDIDIKAN BIOLOGI, 2019)
This research is about descriptive research which propose to recognize students’ perception level in teachers’ teaching method application, to know students’ motivation level while learning biology and to know the relation between students’ perception about teachers’ teaching method application and students’ motivation in learning biology of XI grade students’ of SMAN 3 Pariaman. The researcher will distributed several questionnaires about students’ perception in teachers’ teaching method application and students’ learning motivation. Each questionnaire will content 24 questions for students’ perception and 29 questions for students’ learning motivation. The two lectures of biology department and one biology teacher in SMAN 3 Pariaman will do a validation of these questionnaires. The data analyze in this research will use statistic calculation and correlation which can be use as descriptive analysis. Based on the research analysis result, we conclude that students’ perception in teachers’ teaching method application are good which gain 84% in range 80-89%, and students’ motivation level while learning biology took the high grade which gain 78% in range 61-80% and it have a positive relation and significant between students’ perceptionabout teachers’ teaching method application and the students’ motivation in learning biology of XI grade students of SMAN 3 Pariaman. The relation of perception about teachers’ teaching method application and the students’ motivation in learning biology are stated to be strong which gain 43,56%.  Keywords: Perception, Teaching Method of Teacher, Motivation